Effect of surface nanostructure on tensile and low cycle fatigue behavior of Al 2014 alloy - Chattopadhyay K.; Pandey V.; Srinivas N.C.S.; Singh V. (My University, 2025)
Aluminium alloy 2014 is an important age hardening alloy for aerospace industries. Effect of ultrasonic shot peening (USSP) in peak aged condition of this alloy was studied on its surface microstructure, tensile properties and low cycle fatigue behavior. The structure of the USSP treated specimens, close to surface was characterized by X-ray diffraction and transmission electron microscopy. The top surface region was found to contain nanosize grains of ∼30 nm. Both yield as well as tensile strength was found to increase progressively with increasing duration of shot peening for 10, 15 and 20 minutes. LCF behavior was studied following ultrasonic shot peening for 10 minutes, at three total strain amplitudes (Δt/2) of ±0.4%, ±0.5% and ±0.6%. © Published under licence by IOP Publishing Ltd.